PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA SOSIALISASI POLITIK MASYARAKAT ONLINE/NETIZEN : Studi Netnografi pada Unggahan @pinterpolitik di Instagram - Muhammad Ibnul Hakim, (2022)
This study examines how online communities/netizens use social media Instagram as a means of political socialization. The @pinterpolitik account is an account that provides political news/information that actively provides content every day. This study aims to analyze the online community/netizen response to the @pinterpolitik account as an agent of political socialization. Instagram, which has a comment feature, will generate various kinds of responses from online communities/netizens based on their political knowledge. This study uses a type of qualitative research netnography that helps the author to study the behavior and culture that occurs in the internet world. The object of this research is an upload entitled "the people are satisfied with the president's performance" which has the most comments throughout February 2022. This research shows that there is a formation of attitudes and political orientation of online communities/netizens towards uploads. This is indicated by the various responses given, namely positive (pro), negative (con), and neutral responses. This study is based on the assumption that the @pinterpolitik account can be used as a means of political socialization to be able to provide feedback/responses freely (according to their respective views).